Tinjauan Yuridis Cerai Gugat Akibat Kekerasan Dalam Rumah Tangga (Studi Putusan No. 23/Pdt.G/2015/PN. Lbp) - Eno Karnis Tafanao; Taufik Siregar; Sri Hidayani (JUNCTO: Jurnal Ilmiah Hukum, 2020)
Divorce is the termination of a legal marriage before a court judge based on conditions determined by law. Therefore it is necessary to understand the spirit of the rules regarding divorce and the causes and consequences that may arise after the husband and wife have broken marriages. This type of research is normative juridical research and the nature of this research is descriptive analysis. Factors causing divorce are disputes and quarrels that have occurred continuously then the peak of disputes in the Plaintiff and Defendant's household in 2005 until now the Defendant has left the residence together. Defendant as head of household cannot carry out his obligations as a good head of household. Legal protection for wives who are victims of husband violence is regulated in several laws and regulations, including in the Criminal Code Article 356 of the Criminal Code, in the Marriage Law (Law No. 1, 1974) Article 24. PP No. 9 Tabun 1975 Article 19 letter d and the Law on the Elimination of Domestic Violence (Law No. 23 of 2004). The basis for consideration of the Panel of judges in deciding the case for divorce is case number 23 / Pdt.G / 2015 / PN.Lbp, namely the application of Article 5 letter (b) Number 23 of 2004 concerning the Elimination of Domestic Violence, Article 19 letter (f) of the Regulation Government Number 9 of 1975.